Tracking Enterobacteria, microbiomes, and antibiotic resistance genes from waste to soil with repeated compost applications - Syndia Sadikalay; Laura Cavé; Célia Ducat; Gwénola Mauriello; Mylène Berchel; Didier Boismoreau; Stéphanie Guyomard; Sylvie Nazaret; Antoine Talarmin; Séverine Ferdinand (PLoS ONE, 2025)
The dissemination of antibiotic resistant bacteria (ARB) and genes is one factor responsible for the increasing antibiotic resistance and the environment plays a role in resistance spread. Animal excreta can contribute to the contamination of the environment with ARBs and antibiotics and in some cases, environmental bacteria under antibiotic pressure may acquire antibiotic resistance genes (ARGs) from ARBs by horizontal gene transfer. In Guadeloupe, a French overseas department, organic amendments derived from human and animal waste are widely used in soil fertilization, but their contribution to antibiotic resistance remains unknown. The objective of this study was to evaluate the impact of composting animal and human raw waste and the repeated application of their derived-composts, on the fate of ARGs and antibiotic resistant Enterobacteria, for the first time, in tropical soils of Guadeloupe used for vegetable production. An unculturable approach was used to characterize the bacterial community composition and ARG content from raw waste to composts. A cultivable approach was used to enumerate Enterobacteria, and resistant isolates were further characterized phenotypically and genotypically. Based on this original approach, we demonstrated that the raw poultry droppings exhibited a depletion of Escherichia and Shigella populations during the composting treatment, which was corroborated by the results on the culturable resistant Enterobacteria. Significant differences in the abundance of ARGs were also observed, with some gene levels increasing or decreasing after composting. In addition, other bacterial genera potentially involved in the spread of antimicrobial resistance were identified. Taken together, these results demonstrate that successive applications of raw waste-derived-composts from green waste, sewage sludge, and poultry droppings reshape the Enterobacterial community and influences the abundance of ARGs, with some gene levels increasing or decreasing, in Guadeloupe’s tropical vegetable production soils.